Zinc in commercial marine fish from Peninsular Malaysia: Biomonitoring, health risks, and UNSDGs’ connection - Chee Kong Yap; Khalid Awadh Al-Mutairi (Journal of Fisheries, 2024)
The present study aimed to determine the human health risk (HHR) of zinc (Zn) in forty species of marine commercial fishes sourced from Peninsular Malaysia and available between April and May 2023. These species exhibited concentrations of Zn ranging from 24.1 to 153 mg kg–1 dried weight. These values fell below the maximum allowable limits established by seafood safety guidelines, indicating that the fish are valuable sources of the essential element. The Zn target hazard quotient values were below 1, suggesting that consuming fish containing Zn poses no non-carcinogenic risks. Additionally, it was discovered that the computed estimated weekly Zn intake values were lower than the established provisional allowable weekly Zn intake. It can be inferred that ingesting fish from Peninsular Malaysia would not expose consumers to any detrimental consequences regarding Zn levels. Although this is true, on-going surveillance via Fish Watch (biomonitoring of metal pollution using fish) is imperative to safeguard the well-being of consumers who significantly depend on commercial marine fish imported from Peninsular Malaysia. The study contributes to the achievement of the United Nations Sustainable Development Goals, particularly Goal 3 (Good Health and Well-being) by promoting safe consumption, Goal 12 (Responsible Consumption and Production) through sustainable fishing practices, and Goal 14 (Life Below Water) by emphasizing the importance of protecting marine ecosystems.